SOBRE CINEMA, AMOR E CUIDADO: mulheres negras na direção e na curadoria (Comunicação & Inovação, 2023)
This work examines the curatorial proposal of three events held in 2017, which highlight the plurality of audiovisual production undertaken by black women and their performance in the scope of curatorship. It also analyzes representations of black women, their experiences, care relationships and family ties in three short films. The hypothesis raised is that, in opposition to the prevailing racism and sexism, black Brazilian women have elaborated narratives that articulate memory, affection and belonging; and filmic practices, in which they occupy a leading position.